Network entry phase optimization for WIMAX network - Ghazali, Mohamad Firdaus (2014)
In the last few years, there has been a large growth in wireless broadband communication including Worldwide Interoperability for Microwave Access (WiMAX) technologies. The network entry process in WiMAX is the first process for Subscriber Station (SS) to join the WiMAX network. It referred to the early procedure performed by SS to register with Base Station (BS) that controls the WiMAX network. Scanning to ranging procedure is part of several steps associated with network entry process. The problem of long channel scanning and collision in ranging process can lead to the delay to the access time for initialization and recovery of service between SS and BS connection. Most of the current approaches are focused on reducing the scanning time and optimizing the ranging process but nearly everyone has ignored the influence of system parameters setting. Through this research, a technique is proposed to be used for IEEE 802.16 WiMAX standard with consideration on WiMAX network entry system parameter settings. The simulation environment has been set up to test different configuration condition in WiMAX environment. The intention is to investigate and make recommendation for necessary configuration for IEEE 802.16 standard. Simulation are done using ns-3 simulator and the findings are presented. Simulation results indicate proposed optimum key parameter value of DCD Interval, UCD Interval and Initial Ranging Interval with effect on QoS parameters that will allow the WiMAX network to operate in a higher level of performance and environments.